Analysis of the antioxidant activity of toons sinensis extract and their biological effects on broilers - Zhao, Xiangmin; Du, Baolong; Wan, Minyan; Li, Jinlu; Qin, Shizhen; Nian, Fang; Tang, Defu (Frontiers in Veterinary Science, 2024)
Plant extracts are rich in a variety of nutrients and contain a large number of bioactive compounds, and compared with traditional feed additives, they have advantages such as wide sources, natural safety and rich nutrition. This study employed in vitro antioxidant and animal experiments to comprehensively evaluate the use of Toona sinensis extract (TSE) in broiler production. 508 1-day-old Cobb 500 broilers were randomly assigned to the 7 experimental groups with 6 replications and 12 birds/replicate. Two groups received Vitamin C (VC) 300 g/t and Vitamin E 500 g/t, and five dose groups of TSE received 0, 300, 600, 900, and 1200 g/t of TSE in their feed. The study spanned 42 days, with a starter phase (1-21 days) and a finisher phase (22-42 days). The results showed that compared to ascorbic acid, TSE had the scavenging ability of 2,2-Diphenyl-1-picrylhydrazyl and hydroxyl radical, with IC50 values of 0.6658 mg/mL and 33.1298 mg/mL, respectively. Compared to TSE 0 group, broilers fed with 1200 g/t TSE showed significant weight gain during the starter phase and increased the feed-to-weight gain ratio during both the starter and finisher phases. Additionally, broilers receiving 1200 g/t TSE had enhanced dry matter and organic matter utilization. Concerning meat quality, broilers in the 1200 g/t TSE group demonstrated increased cooked meat yield, and pH value, as well as higher antioxidant capacity (T-AOC), dismutase (SOD), and glutathione peroxidase (GSH-PX) in serum. In addition, there was no significant difference in ileal microflora due to TSE supplementation. In summary, this study confirms the positive impact of a dietary inclusion of 1200g/t TSE on broiler growth, meat quality, and serum antioxidants.